2016
DOI: 10.1007/s00125-016-4061-x
|View full text |Cite
|
Sign up to set email alerts
|

Knockout maternal adiponectin increases fetal growth in mice: potential role for trophoblast IGFBP-1

Abstract: Aims/hypothesis The main objective of this study was to investigate whether maternal adiponectin regulates fetal growth through the endocrine system in the fetal compartment. Methods Adiponectin knockout (Adipoq−/−) mice and in vivo adenovirus-mediated reconstitution were used to study the regulatory effect of maternal adiponectin on fetal growth. Primary human trophoblast cells were treated with adiponectin and a specific peroxisome proliferator-activated receptor α (PPARα) agonist or antagonist to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 50 publications
1
35
1
Order By: Relevance
“…Indeed, chronic infusion of full-length ADN to normal-weight pregnant mice decreased fetal weight, demonstrating that maternal ADN limits fetal growth (34). This conclusion was recently confirmed in elegant studies in which knockdown of the maternal ADN gene resulted in increased fetal growth (35,36). We have further demonstrated that ADN regulates placental function mediated by activation of trophoblast peroxisome proliferator-activated receptor a (PPAR-a) signaling, which increases ceramide synthesis resulting in inhibition of insulin receptor substrate 1 (IRS-1) (33).…”
mentioning
confidence: 79%
“…Indeed, chronic infusion of full-length ADN to normal-weight pregnant mice decreased fetal weight, demonstrating that maternal ADN limits fetal growth (34). This conclusion was recently confirmed in elegant studies in which knockdown of the maternal ADN gene resulted in increased fetal growth (35,36). We have further demonstrated that ADN regulates placental function mediated by activation of trophoblast peroxisome proliferator-activated receptor a (PPAR-a) signaling, which increases ceramide synthesis resulting in inhibition of insulin receptor substrate 1 (IRS-1) (33).…”
mentioning
confidence: 79%
“…The body weight of foetuses from adiponectin (−/−) dams was significantly greater than that of wild type dams at both embryonic day (E)14.5 and (E)18.5. In addition to nutrient supply, maternal adiponectin inhibits foetal growth by increasing IGFBP-1 expression in trophoblast cells [143].…”
Section: Foetus Growthmentioning
confidence: 99%
“…Analysis of fetal weight and body composition showed that the maternal high-fat diet increased the weight and fat mass of offspring of WT dams, while the offspring of knockout dams had a lower weight and fat mass. In a recent study [13], the offspring of adiponectin gene–knockout dams exhibited a greater weight and fat mass than WT offspring. Furthermore, chronic infusion of adiponectin in pregnant mice has been shown to decrease fetal growth, possibly by reducing amino acid transporter activity and expression [14].…”
Section: Introductionmentioning
confidence: 99%